Successful treatment of Yersinia pseudotuberculosis hepatitis in a cat presenting with neurological abnormalities. Issue 1 (May 2019) - Thompson, Dan
Case summary: A 3-year-7-month-old female neutered domestic shorthair cat was presented for further investigation of acute-onset neurological abnormalities, including marked decreased mentation, ataxia and abnormal cranial nerve responses, with concurrent marked pyrexia (40ºC). Initial blood testing was non-specific with mild-to-moderate increases in alanine aminotransferase (ALT) (194 IU/l; reference interval [RI] 17–62 IU/l), aspartate aminotransferase (AST; 150 IU/l [RI 0–51 IU/l]) and total bilirubin (20 µmol/l; RI 0–11 µmol/l), and neutropenia (1.17 ×10 9 /l; RI 2.5–12.5 ×10 9 /l). Brain MRI and cerebrospinal fluid analysis were unremarkable and Toxoplasma serology was negative. Worsening of hepatic biochemical parameters (ALT 265 IU/l, AST 205 IU/l, total bilirubin 42.9 µmol/l) led to further investigations for liver disease, including ultrasound, fine-needle aspirate cytology, histology, fluorescent in situ hybridisation and culture of liver tissue and bile, resulting in a diagnosis of Yersinia pseudotuberculosis hepatitis. The cat was treated with a combination of potentiated amoxicillin (62.5 mg PO q12h), marbofloxacin (5mg PO q24h) and combined s-adenosyl methionine (SAMe)/silybin (90 mg PO q24h), and made a full recovery. Follow-up over 14 months identified a persistent mild increase in ALT, despite no apparent ongoing disease. Relevance and novel information: Yersinia pseudotuberculosis hepatitis should be considered as a differential diagnosis in cats presenting with acute-onset neurological signs, and, when diagnosed, can be successfully treated with a combination of marbofloxacin, potentiated amoxicillin and SAMe/silybin. This is the first such case treated successfully with licensed veterinary antimicrobials and the first instance where Y pseudotuberculosis hepatitis has presented with primarily neurological clinical signs.